Pelatihan Perakitan Battery Pack Lithium Ion 18650 Untuk Guru SMK di Kabupaten Jember - Cahyaning Nur Karimah; Dwi Djoko Suranto; Dicky Adi Tyagita; Alex Taufiqurrohman Zain; Aditya Wahyu Pratama; Dety Oktavia Sulistiono; Faruq Avero Azhar (Indonesian Journal Publisher, 2023)
The battery pack is one of the potential parts to be developed on a laboratory scale. The battery pack is a unit of several rechargeable battery cells assembled in series-parallel. Battery packs are generally equipped with a Battery management system (BMS). BMS is an electronic circuit that functions to limit the current and voltage entering the battery in the charging process when the battery is full. This will certainly prevent short circuits and increase battery life. As one of the vocational education institutions, SMK are expected to be able to read and take advantage of existing opportunities related to the increasing number of national vehicles and the acceleration of battery-based electric vehicles according to Presidential Regulation number 5 of 2019. In line with the link and match agenda of vocational universities with SMK, this community service team took the initiative to collaborate with SMK together with PTV as a facilitator and SMK teachers as SMK partners. This training activity begins with preparing an electric vehicle battery pack prototype and testing it in the automotive engine laboratory, engineering drawing and computing studio and DUDI partner workshops. At the end of the training, an evaluation was carried out in the form of a questionnaire on the success of the battery assembly training activities using a linkert scale. As a result, the battery assembly training which activities are measuring and monitoring battery pack, increase the knowledge of teachers about how to assemble 18650 lithium ion batteries according to the requirements of the motor that is used.